Perceived overqualification and deviant innovation behavior: The roles of creative self-efficacy and perceived organizational support - Lu, Lu; Luo, Tanghong; Zhang, Yajun (Frontiers in Psychology, 2023)
Employees’ perceived overqualification (POQ) is prevalent in organizations and has drawn increasing attention from both researchers and practitioners. Drawing from social cognitive theory, the purpose of this study is to extend existing understanding of the consequences of POQ by examining how and when POQ leads to deviant innovation behavior. This study hypothesizes that employees’ POQ indirectly impacts deviant innovation through enhanced creative self-efficacy (CSE), and that perceived organizational support (POS) strengthens this indirect relationship. Using data collected from 286 employees in China at two time points, this study found support for our hypotheses that POQ is positively related to CSE, and that CSE mediates the relationship between POQ and deviant innovation behavior. In addition, this study found that POS moderates the relationship between POQ and CSE, as well as the indirect effect of POQ on deviant innovation behavior via CSE. The theoretical and practical implications of our findings and future research directions are discussed.